An Exploration of Retail Line-Managers and Work-Life Balance Experiences, Strategies and Responsibilities - Reilly, Justine C (2018)
The concept of work-life balance is generating increasing academic and public interest as research highlights its positive links to organisational commitment, performance and job-satisfaction. However, achieving a work-life balance has been noted as problematic for employees in the retail sector, amidst a traditional service sector culture of small budgets, long-hours and emotionally and physically demanding work. As middle managers are rarely studied in work-life balance research, the aim of this study is to explore retail line-manager experiences of work-life balance. More specifically, the research aims to explore how retail line-managers take responsibility for their work-life balance and how they attempt to personally manage it. The research aims are addressed through in-depth qualitative interviews with retail line-managers in a large retail organisation. The study suggests that the work-life balance of retail managers is significantly shaped by the nature of their job-role and the retail sector, particularly as underlying cultural norms and unclear expectations result in line-managers undertaking excessive workloads. This also influenced the way retail line-managers attempted to manage their work-life balance. The study also found that there were varied line-manager attitudes towards work-life balance responsibility, with some believing that managing work-life balance is totally their own responsibility and others claiming retail employers should be more responsible. Despite the varied beliefs, on the whole, most of the line-managers claimed that their work-life balance could be better facilitated by their organisation.